"NAPOLEON OF THE EAST", OR "NADER OF THE WEST" - Jafarov Rahil Maharram; Askarov Aslan Khudaverdi; Agarzayev Tugay Feyruz; Hasanova Fatima Elnur; Hajiyeva Asina Aydin; Guluyeva Guler Intizam; Allahverdiyeva Nargiz Parviz; Hasanova Sona Seymur; Aliyeva Gunesh Aftandil (Theoretical Hypotheses and Empirical Results, 2025)
Nader Shah Afshar was an Azerbaijani ruler belonging to the Afshar Turkic tribe. He holds a significant place in Azerbaijani and world history due to his personality, military achievements, efforts at religious reform within Islam, state-building reforms, and foreign policy strategy. It is therefore not surprising that French Emperor Napoleon Bonaparte considered Nader Shah Afshar as his ideal. Unfortunately, due to historical manipulation and the misrepresentation of facts, Nader Shah Afshar is widely known in the world as the "Iranian ruler." The authors of this article aim to correct this misinformation and prove that Nader Shah was not the "Napoleon of the East," but rather, Napoleon Bonaparte was the "Nader of Europe."